KORESPONDENCJA SERDECZNA. STANISŁAW PIGOŃ - JULIUSZ WIKTOR GOMULICKI - Nowoszewski, Roman (Colloquia Litteraria, 2019)
Stanisław Pigoń - Juliusz Wiktor Gomulicki The second part of the correspondence between professor Stanisław Pigoń and Juliusz Wiktor Gomulicki contains letters from 1949-1956. The earliest four letters were published in „CL” before. The whole collection contains 58 items; the letters deal primarily with the biography and writings of Cyprian Norwid.